(untitled) (Tzintzun, Revista de Estudios Históricos, 2024)
In 1820, Rafael del Riego started an uprising in Spain to establish a liberal government in the Spanish Empire. This concluded the Sexenio Absolutista, giving way to the Trienio Liberal. In Europe, the revolutionary spread led Portugal, Naples and Piedmont to follow the same path, seeking to replace their absolute monarchies with constitutional governments. This would cause the great European monarchies, allied under the banner of the Holy Alliance, to initiate an interventionist policy to prevent the revolution from crossing their borders. Shortly afterwards, Austria invaded Naples, abolishing its constitutional government. This article discusses how this interventionist policy was reflected in the public opinion of the first Mexican Empire (1821-1823). How the possibility of an alliance between Fernando VII and the coalited monarchic powers implanted the fear of an imminent Spanish invasion through the Fort of San Juan de Ulúa, in Veracruz.